Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/jeb.13193
|View full text |Cite
|
Sign up to set email alerts
|

Experimental manipulation reveals a trade‐off between weapons and testes

Abstract: Theory predicts a trade-off between sexually selected weapons used to secure mates and post-copulatory traits used to maximize fertilization success. However, individuals that have a greater capacity to acquire resources from the environment may invest more in both pre-and post-copulatory traits, and trade-offs may not be readily apparent. Here, we manipulate the phenotype of developing individuals to examine allocation trade-offs between weapons and testes in Mictis profana (Hemiptera: Coreidae), a species wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 51 publications
3
35
0
Order By: Relevance
“…Thus, these results challenge the idea that morphological tradeoffs might be limited to closed systems, such as the pupae of holometabolous species (Moczek and Nijhout 2004;Tomkins et al 2005). In a study conducted shortly after this one, Somjee et al (2017) found evidence of a similar weapons-testes trade-off in another hemimetabolous insect in the same family (Coreidae). It is possible that resource allocation trade-offs are as prevalent in hemimetabolous species as the Holometabola.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Thus, these results challenge the idea that morphological tradeoffs might be limited to closed systems, such as the pupae of holometabolous species (Moczek and Nijhout 2004;Tomkins et al 2005). In a study conducted shortly after this one, Somjee et al (2017) found evidence of a similar weapons-testes trade-off in another hemimetabolous insect in the same family (Coreidae). It is possible that resource allocation trade-offs are as prevalent in hemimetabolous species as the Holometabola.…”
Section: Discussionmentioning
confidence: 88%
“…In a study conducted shortly after this one, Somjee et al. () found evidence of a similar weapons‐testes trade‐off in another hemimetabolous insect in the same family (Coreidae). It is possible that resource allocation trade‐offs are as prevalent in hemimetabolous species as the Holometabola.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Typically, ejaculate investment is negatively correlated with traits associated with mate monopolization (e.g., Somjee et al. ) and, to a lesser extent, mate attraction (for a review see Simmons et al. ).…”
Section: Discussionmentioning
confidence: 99%